PENGARUH EKSPOR, IMPOR DAN PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Dela Purnama; Novie Al Muhariah; Andri Irawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2026)
This study aims to determine the effect of exports, imports, and foreign direct investment on economic growth in Indonesia. The data used in this study were obtained from the Central Bureau of Statistics (BPS) for the period 2015–2024. The analytical method applied is quantitative analysis using multiple linear regression. Data processing was conducted through statistical testing and classical assumption testing. However, during the analysis process, a high multicollinearity symptom was found between the export and import variables. Therefore, the import variable was eliminated to obtain more stable and valid results, and the analysis continued with export and foreign direct investment as the independent variables. The results show that simultaneously (F-test), export and foreign direct investment significantly influence economic growth in Indonesia. Partially (t-test), both export and foreign direct investment have a positive and significant effect on economic growth. The coefficient of determination (R²) is 0.763, indicating that the joint contribution of export and foreign direct investment to the variation in economic growth is 76.3%, while the remaining 23.7% is influenced by other factors not examined in this study, such as household consumption, government expenditure, domestic investment, labor conditions, exchange rate stability, inflation, and global economic development.